2019
DOI: 10.3171/2019.4.focus19235
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient slow-flow suppression mimicking aneurysm wall enhancement in magnetic resonance vessel wall imaging: a phantom study

Abstract: OBJECTIVEMR vessel wall imaging (VWI) is increasingly performed in clinical settings to support treatment decision-making regarding intracranial aneurysms. Aneurysm wall enhancement after contrast agent injection is expected to be related to aneurysm instability and rupture status. However, the authors hypothesize that slow-flow artifacts mimic aneurysm wall enhancement. Therefore, in this phantom study they assess the effect of slow flow on wall-like enhancement by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 18 publications
1
40
1
Order By: Relevance
“…The low positive predictive value of AWE and aneurysm instability may be partially explained by the insufficient slow-flow suppression by the currently available HR VW-MRI sequences. A phantom-based study by Cornelissen et al showed that slow flow along the aneurysm wall mimics AWE [ 39 ]. Thus, caution must be taken when interpreting HR VW-MRI studies.…”
Section: Discussionmentioning
confidence: 99%
“…The low positive predictive value of AWE and aneurysm instability may be partially explained by the insufficient slow-flow suppression by the currently available HR VW-MRI sequences. A phantom-based study by Cornelissen et al showed that slow flow along the aneurysm wall mimics AWE [ 39 ]. Thus, caution must be taken when interpreting HR VW-MRI studies.…”
Section: Discussionmentioning
confidence: 99%
“…Cornelissen et al assumed that wall enhancement is not causally linked with inflammatory processes but rather attributable to method-inherent failure of blood signal suppression in low-flow conditions [ 40 , 41 ]. The results of our study suggest that inflammatory changes probably add to the extent of wall enhancement, and that even without convincing proof of a causal link, wall enhancement indicates the presence of a hemodynamic environment promoting inflammatory and degenerative processes and might therefore still serve as a surrogate marker for aneurysm wall instability.…”
Section: Discussionmentioning
confidence: 99%
“…38 Advanced MRA techniques and vessel wall imaging have theoretical roles in aneurysm risk assessment, but they remain investigational. 17,25 Imaging is important in determining which therapeutic options are optimal for individual aneurysms. Although DSA remains the gold standard for imaging UIAs, CTA and MRA are more often being used to make surgical decisions without DSA due to their greater availability and noninvasiveness.…”
Section: Uias: Who Is Imaged and Why?mentioning
confidence: 99%